Effect on intra qcular pressure and hemodynamic response with endotrachealintumation vs laryngeal mask airway insertion in children. - Tabadar, Sushila (2000)
SUMMARY: PHD. MD proved that LMA, J. ButlerG.s. Clark, D.S. IIuges and P.J. Becon also showed in their study that LMA caused minimum rise of IOP and hemodynamic changes as compared to ETT at the time of insertion as well as removal and incidence of cough was also much less with it at the awakening caused less rise of IOP as compared to ETT in eye cause during insertion. R. IIolden, CD.G.M. Morsman period. So besides using only pharmacological means to control IOP, LMA can be useful which has already been proved by many studies. Our randomized prospective study of thirty eight patients two devided groups of either group A (LMA) or group B (ETT) for comparison of IOP and hemodynamic responses before and after the use of separate device can help to conclude the fact LMA is far better than ETT for eye cases because though there were no significant difference between age, sex, and weight distribution between 2 groups but there was a significant rise of IOP after ETT Vs LMA with P value 0.00 Vs 0.42 to 0.79 In case of hemodynamics the statistical result did not show any clear cut value Immediately after 1 minute of LMA insertion HR rise was significant i.e. P value 0.00 but not after that. In ETT group increase of HR was constant for 5 minutes with P value 0.00. From this we can draw an inference that ETT causes more HR change for long period. Similarly SBP and DBP in 2 groups showed that within 1 and 3 minutes of LMA insertion there was a significant rise of SBP with P value 0.003 and 0.008 and DBP with P value 0.002 and 0.004 but not till 5 minutes. In ETT group SBP and DBP after intubation was high all the time with P value 0.00. From this result also we can say that ETT causes significant rise of HR and BP for a long time. Complication can arise in both the groups for which we need to be careful. For the better result large sample size and more parameters for study will be beneficial.